Językowa definicja sytuacji zawarta w tekście obrzędów sakramentu małżeństwa w perspektywie goffmanowskiej. - Kamasa, Victoria (Investigationes Linguisticae, 2008)
The article is to describe the definition of the situation formed by the language of “Rituals of the Holy Matrimony Adjusted to the Customs of Polish Dioceses”. The main question is hence: “What definition of the situation is created by the text of the holy matrimony rituals in the Roman Catholic Church”. The analysis are conducted from a sociological perspective created by E. Goffman and called ”dramaturgical perspective”. According to this perspective interactions between people are seen as a performance given by a performer or a team of performers to make an impression on other people (the public). The research question is answered with a help of the theory of conceptual metaphors, the speech acts theory and the theory of conversational implicature. After recognizing main impressions, means of persuasion which were used for creating them are identified and described. The last part describes so-called impression management in analysed rituals.